2022
DOI: 10.1111/jgs.17721
|View full text |Cite
|
Sign up to set email alerts
|

Perceived dementia risk and advance care planning among older adults

Abstract: Background Although advance care planning (ACP) is beneficial if dementia develops, and virtually all older adults are at risk for this disease, older adults do not consistently engage in ACP. Health behavior models have highlighted the importance of perceived susceptibility to medical conditions in motivating behavior. Following these models, we sought to determine how often older adults believe they are not at risk of developing dementia and to examine the association between perceived dementia risk and ACP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our review identified studies from countries across European, Oceanian, Asian, and North American regions where life expectancy is typically longer [35]. We acknowledge that the nature of work for older adults' care personnel in these regions will differ, as people spend more time in need of care, so knowledge of advance care planning and palliative care is required [95][96][97]. It is further noted that aside from population size and life expectancy, there are differences between countries regarding social security systems, impact of religion, and local economic situations [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Our review identified studies from countries across European, Oceanian, Asian, and North American regions where life expectancy is typically longer [35]. We acknowledge that the nature of work for older adults' care personnel in these regions will differ, as people spend more time in need of care, so knowledge of advance care planning and palliative care is required [95][96][97]. It is further noted that aside from population size and life expectancy, there are differences between countries regarding social security systems, impact of religion, and local economic situations [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Dementia is a case in point. The trajectory of incapacity in cognitive impairment and dementia, as the authors of the study in JAGS note, is often “insidious and prolonged.” 1 Even allowing for disruptive events that alter the trajectory of decline in dementia, 4 there is rarely a clear demarcation between a state of health and a state of serious illness. The same is true of patients at high risk of dementia.…”
Section: Figurementioning
confidence: 99%
“…The study by Lee and colleagues in this issue of JAGS finds that older adults with a higher perceived risk of dementia are more likely to have engaged in advance care planning than those with no perceived risk. 1 However, among older adults with a perceived risk of >50%, engagement in advance care planning was far from universal.…”
mentioning
confidence: 99%
“…This includes difficult decisions about further care, nursing, and possible treatments or therapies (Caron et al, 2006;Lord et al, 2015). A living will and powers of attorney can be supportive here, although these are often not available in reality (e.g., Lee et al, 2022). This has an additional psychological effect on the relatives responsible for the decision, who are already in a stressful situation (Alltag et al, 2019;Bohnet-Joschko & Bidenko, 2021).…”
Section: Introductionmentioning
confidence: 99%